Pick's Theorem and Convergence of Multiple Fourier Series. Issue 1 (29th December 2020) - Brandolini, L.; Colzani, L.; Robins, S.; Travaglini, G.
Abstract: We add another brick to the large building comprising proofs of Pick's theorem. Although our proof is not the most elementary, it is short and reveals a connection between Pick's theorem and the pointwise convergence of multiple Fourier series of piecewise smooth functions.